2016
DOI: 10.1017/s0022029916000601
|View full text |Cite
|
Sign up to set email alerts
|

Is lack of antibiotic usage affecting udder health status of organic dairy cattle?

Abstract: This research communication aimed to compare somatic cell count (SCC), the main marker of udder health status, in organic farms not using antibiotics (O, n = 6), organic farms using antibiotics (OA, n = 7) and conventional farms (CA, n = 5) using antibiotic treatments, all of them at pasture. SCC was statistically significantly higher in O (173780) compared to CA (93325) and OA (107152). Milk yield had a significant diluting effect on SCC and differences between groups increased with parities. Stratified analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
(16 reference statements)
1
17
0
Order By: Relevance
“…1). Previous studies in Spain have indicated poorer udder health status on organic farms that favour the use of alternative therapies over use of antibiotics, especially in older cows (Orjales et al, 2016); indeed, the same study concluded that although organic farming aims to reduce the use of antibiotics, treatment must be used in older cows to maintain udder health status. As already mentioned, older cows on organic farms are at a greater risk of suffering chronic subclinical mastitis, which is very difficult to control unless antibiotic therapy is used.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…1). Previous studies in Spain have indicated poorer udder health status on organic farms that favour the use of alternative therapies over use of antibiotics, especially in older cows (Orjales et al, 2016); indeed, the same study concluded that although organic farming aims to reduce the use of antibiotics, treatment must be used in older cows to maintain udder health status. As already mentioned, older cows on organic farms are at a greater risk of suffering chronic subclinical mastitis, which is very difficult to control unless antibiotic therapy is used.…”
Section: Resultsmentioning
confidence: 91%
“…1). The SCC has been reported to increase significantly with lactation number on organic dairy farms in northern Spain, particularly farms on which antibiotic therapy is not used (Orjales et al, 2016) and has been related to chronic infection after several lactation periods (Villar & López-Alonso, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As was expected, in the present study LS and percentage of SCC surpassing >200,000 somatic cells increased with lactation number in all breed groups (Reneau, ). These increases become more evident when cows survive during many lactations (Tancin, ) as in organic systems (Orjales Galdo et al, ; Orjales et al, ). Studies carried out in organic and pasture‐based systems to evaluate the effect of breed on SCC, LS or udder health produce inconclusive results, although only broad comparisons can be made.…”
Section: Discussionmentioning
confidence: 99%
“…However, this result is clearly dependent of whether or not organic farmers chose to keep using antibiotics at all. Organic farms that chose to abolish the use of antibiotics had higher somatic cell counts (a proxy measure of poor udder health and of subclinical mastitis) compared to conventional farms, but no differences were found between Spanish organic farms that use antibiotics (when needed) and conventional farms [ 182 ]. These results confirm previous work showing either no differences in mastitis prevalence or treatments between both systems [ 171 , 183 ] or reduced prevalence of mastitis in organic herds [ 175 , 184 ].…”
Section: Healthmentioning
confidence: 99%